2018
DOI: 10.29328/journal.cjog.1001014
|View full text |Cite
|
Sign up to set email alerts
|

Immediate postplacental insertion of intrauterine contraceptive device (copper 375) and its complications in term of expulsion, infection and perforation

Abstract: Objective: To determine the complications (infection, perforation and expulsion rate) of immediate postplacental insertion of intrauterine contraceptive device (Multiload Copper375) in postnatal patients. Methods: A case series study was conducted between October 28, 2014 to April 30, 2018 in obstetrics and gynaecology department, Civil Hospital Karachi,-+ Informed consent was taken. Intrauterine contraceptive device (Multiload) was inserted immediately within 10 min after delivery of placenta. These women wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…1,2 Benish et al reported 5.5% of expulsion rate of post-vaginal delivery compared to 3.4% of cesarean section. 20 The expulsion rate of post-placental IUD insertion using Kelly forceps had been reported in two studies from India. Gupta et al reported the expulsion rate was 14.3% at 6 weeks, 2.9% at 3 months, and 0% at 6 months, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 Benish et al reported 5.5% of expulsion rate of post-vaginal delivery compared to 3.4% of cesarean section. 20 The expulsion rate of post-placental IUD insertion using Kelly forceps had been reported in two studies from India. Gupta et al reported the expulsion rate was 14.3% at 6 weeks, 2.9% at 3 months, and 0% at 6 months, respectively.…”
Section: Discussionmentioning
confidence: 98%